Environmentally Robust Black Phosphorus Nanosheets in Solution: Application for Self‐Powered Photodetector. (21st March 2017) - Ren, Xiaohui; Li, Zhongjun; Huang, Zongyu; Sang, David; Qiao, Hui; Qi, Xiang; Li, Jianqing; Zhong, Jianxin; Zhang, Han
Abstract : Large‐size 2D black phosphorus (BP) nanosheets have been successfully synthesized by a facile liquid exfoliation method. The as‐prepared BP nanosheets are used to fabricate electrodes for a self‐powered photodetector and exhibit preferable photoresponse activity as well as environmental robustness. Photoelectrochemical (PEC) tests demonstrate that the current density of BP nanosheets can reach up to 265 nA cm −2 under light irradiation, while the dark current densities fluctuate near 1 nA cm −2 in 0.1 M KOH. UV–vis and Raman spectra are carried out and confirm the inherent optical and physical properties of BP nanosheets. In addition, the cycle stability measurement exhibits no detectable distinction after processing 50 and 100 cycles, while an excellent on/off behavior is still preserved even after one month. Furthermore, the PEC performance of BP nanosheets‐based photodetector is evaluated in various KOH concentrations, which demonstrates that the as‐prepared BP nanosheets may have a great potential application in self‐powered photodetector. It is anticipated that the present work can provide fundamental acknowledgement of the performance of a PEC‐type BP nanosheets‐based photodetector, offering extendable availabilities for 2D BP‐based heterostructures to construct high‐performance PEC devices. Abstract : 2D black phosphorus (BP) nanosheets are fabricated as self‐powered photodetector in KOH electrolyte. The photoelectrochemical tests demonstrate that BP nanosheets achieve preferable photoresponse activity as well as environmental robustness. Besides this, the photoresponse performance of BP nanosheets can be further optimized by adjusting KOH concentrations. This work presents a fundamental acknowledgement of the photoresponsivity of BP nanosheets for self‐powered photodetecting.